1980
DOI: 10.1002/pol.1980.180180208
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of alkyl‐aromatic polyimides (polyalkanimides)

Abstract: Polyalkane imides based on 3,3′,4,4′‐diphenyloxidetetracarboxylic, pyromellitic and 1,4,5,8‐naphthalenetetracaboxylic acids, and aliphatic diamines containing 4, 6, 8, 10, or 12 methylene groups have been studied. Relations governing the effect of structure on solubility, heat resistance, density, and crystallizability have been established. Conformation analysis has been carried out and models of the macromolecules have been constructed. The morphology of the crystalline polymers has been studied. For the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Wholly aromatic polyimides are superengineering plastics which exhibit excellent thermal and mechanical properties and have been used widely in aerospace, electronics, and other industries over the past 3 decades. , Aliphatic−aromatic polyimides derived from aliphatic diamines (hereafter aliphatic polyimides), which were first prepared in the mid 1950s, also have great potential for superengineering plastics; however, the information on their synthesis and properties are known to a lesser extent. Some aliphatic polypyromellitimides were obtained by the melt polycondensation of the nylon-salt-type monomers composed of aliphatic diamines and pyromellitic acid (PMA) or its diester diacid or by the high temperature solution polycondensation of aliphatic diamines with pyromellitic dianhydride (PMDA) in nitrobenzene, and their properties were reported only briefly in the literature. Koning et al reported the synthesis of several aliphatic polyimides by a conventional two-step process from aromatic dianhydrides including PMDA, 3,3‘,4,4‘-biphenyltetracarboxylic dianhydride, 3,3‘,4,4‘-benzophenonetetracarboxylic dianhydride (BTDA), 4,4‘-oxydiphthalic anhydride, and 4,4‘-sulfonyldiphthalic anhydride. Although the properties of the BTDA-based polyimides were investigated in detail, less information is available on the properties of aliphatic polyimides derived from the other aromatic dianhydrides …”
Section: Introductionmentioning
confidence: 99%
“…Wholly aromatic polyimides are superengineering plastics which exhibit excellent thermal and mechanical properties and have been used widely in aerospace, electronics, and other industries over the past 3 decades. , Aliphatic−aromatic polyimides derived from aliphatic diamines (hereafter aliphatic polyimides), which were first prepared in the mid 1950s, also have great potential for superengineering plastics; however, the information on their synthesis and properties are known to a lesser extent. Some aliphatic polypyromellitimides were obtained by the melt polycondensation of the nylon-salt-type monomers composed of aliphatic diamines and pyromellitic acid (PMA) or its diester diacid or by the high temperature solution polycondensation of aliphatic diamines with pyromellitic dianhydride (PMDA) in nitrobenzene, and their properties were reported only briefly in the literature. Koning et al reported the synthesis of several aliphatic polyimides by a conventional two-step process from aromatic dianhydrides including PMDA, 3,3‘,4,4‘-biphenyltetracarboxylic dianhydride, 3,3‘,4,4‘-benzophenonetetracarboxylic dianhydride (BTDA), 4,4‘-oxydiphthalic anhydride, and 4,4‘-sulfonyldiphthalic anhydride. Although the properties of the BTDA-based polyimides were investigated in detail, less information is available on the properties of aliphatic polyimides derived from the other aromatic dianhydrides …”
Section: Introductionmentioning
confidence: 99%
“…Aromatic polyimides have been well known for many years as high-temperature and high-performance polymers and have found many applications in aerospace, electronics, and other industries.1-2 Polyimide investigations have been carried out mainly with wholly aromatic polyimides, whereas relatively little detailed information is available in regard to the synthesis and properties of aliphatic diamine-based polyimides (hereafter aliphatic polyimides). [3][4][5] Aliphatic polyimides were first prepared in 1955 by the melt polycondensation of the salt composed of an aliphatic diamine and an aromatic tetracarboxylic acid or of a diamine and a diester diacid. 3-6-7 In addition, there is a brief indication that aromatic polyimides were also prepared via the corresponding salt monomers by thermal polycondensation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of crystallinity could serve as an effective approach to improve the thermal stability, solvent resistance, and mechanical properties of polymers. Hence, development of semicrystalline polyimides has attracted considerable attention for these years [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. The most well-known semicrystalline polyimides include LaRC-CPI developed by NASA [23,24,25,26,27,28], New-TPI developed by Mitsui Toatsu Chemicals [29,30,31,32], R-BAPB type polyimides developed by the Russian Academy of Sciences [33,34,35,36], and some other semicrystalline polyimides developed by the University of Akron [37,38,39,40] and Virginia Polytechnic Institute [41,42,43,44,45].…”
Section: Introductionmentioning
confidence: 99%